2023
DOI: 10.1039/d2ra07733g
|View full text |Cite|
|
Sign up to set email alerts
|

An overview of atmospheric water harvesting methods, the inevitable path of the future in water supply

Abstract: Although science has made great strides in recent years, access to fresh water remains a major challenge for humanity due to water shortage for two-thirds of the world's population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 149 publications
0
8
0
Order By: Relevance
“…Today, population growth, soaring living standards, global warming, and the uncertainties of climatic variability have already affected water availability, demands, and uneven water distribution, causing more than two billion people to live in waterdeficient areas or during water crises [41,42]. Different strategies and dedicated materials were researched for water extraction from atmospheric air devoted to the enhancement of water productivity and versatility in applications [30][31][32][33][34][43][44][45][46][47] particularly in arid regions for the alleviation of water scarcity [42]. While storing water is important, there are limits to how much we can store.…”
Section: Discussionmentioning
confidence: 99%
“…Today, population growth, soaring living standards, global warming, and the uncertainties of climatic variability have already affected water availability, demands, and uneven water distribution, causing more than two billion people to live in waterdeficient areas or during water crises [41,42]. Different strategies and dedicated materials were researched for water extraction from atmospheric air devoted to the enhancement of water productivity and versatility in applications [30][31][32][33][34][43][44][45][46][47] particularly in arid regions for the alleviation of water scarcity [42]. While storing water is important, there are limits to how much we can store.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them are already mature and can be found on the market [36], while others are still in the developing stage. An exhaustive review of the field state-of-the-art techniques can be found in many recent works, such as the work published by the authors of [37], which deeply analyzes the current techniques development, or that published by the authors of [38], which underlines the importance of the development of atmospheric water harvesting in the future, or that published by the authors of [39], which particularly focused on the water extraction from air analyses in remote areas of the planet.…”
Section: Water Extraction From the Air: A Brief Summary Of The Curren...mentioning
confidence: 99%
“…MOF-303 was first synthesized in 2018 by the Yaghi group [ 5 ], and so far, there are not many papers devoted to this MOF. Moreover, studies on MOF-303 have been mainly dedicated to atmospheric water harvesting (AWH) [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], and this MOF has been identified as one of the most efficient mediums for this application [ 21 ]. It quickly turned out that it is also a very good adsorbent for CO 2 [ 22 ], SO 2 [ 23 ], NH 3 [ 24 ], C 2 H 2 [ 25 ], Xe [ 26 ], alcohols [ 27 ], particulate matters [ 28 ], water contaminants [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ], separation [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], and other applications [ 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%